2020
DOI: 10.1016/j.actbio.2020.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Tough combinatorial poly(urethane-isocyanurate) polymer networks and hydrogels synthesized by the trimerization of mixtures of NCO-prepolymers

Abstract: The development of tough hydrogels is an essential but challenging topic in biomaterials research that has received much attention over the past years. By the combinatorial synthesis of polymer networks and hydrogels based on prepolymers with different properties, new materials with widely varying characteristics and unexpected properties may be identified. In this paper, we report on the properties of combinatorial poly(urethane-isocyanurate) (PUI) type polymer networks that were synthesized by the trimerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…The measured swelling ratios in tough hydrogels are highly sensitive to their chemical nature and environmental conditions (pH, temperature, etc) . Nonetheless, the values found in this study are consistent with those found for physically cross-linked tough polyurethane …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The measured swelling ratios in tough hydrogels are highly sensitive to their chemical nature and environmental conditions (pH, temperature, etc) . Nonetheless, the values found in this study are consistent with those found for physically cross-linked tough polyurethane …”
Section: Resultssupporting
confidence: 88%
“…67 Nonetheless, the values found in this study are consistent with those found for physically cross-linked tough polyurethane. 10 DSC analyses on the specimen immersed in water for different times were performed to investigate the thermal stability of the switching domains, namely, the POE crystal. In the dry state, the copolymers show endothermic peaks at 46.4, 47.6, and 44.1 °C for PU-5-30, PU-8-30, and PU-5-40, respectively, which are attributed to the melting of PEO SS crystals ( PEO T m ) (Figure 8b, Supporting Information Figure S7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isocyanurates, heterocyclic structures of 1,3,5-triazine-2,4,6-trione, formed via cyclotrimerization of isocyanates are widely used to enhance the physical properties of a variety of polyurethanes. Whereas the controlled trimerization of aliphatic isocyanates is used for the preparation of isocyanurate cross-linkers for high-performance polyurethane coatings, the cyclotrimerization of aromatic isocyanates into polyisocyanurate (PIR) structures is used to improve the thermal stability and flame retardancy of polyurethane rigid foams. The initial molar ratio of functional groups and especially the type of catalyst are the main factors influencing the formation of PIR structures. The most commonly used catalysts in industrial applications are based on carboxylates, such as potassium acetate, potassium 2-ethylhexanoate, trimethyl hydroxypropyl ammonium formate, or phenolate such as 2,4,6-tris­(dimethylaminomethyl)­phenol. ,− The various industrial and commercial applications of isocyanurate-based polyurethane materials have attracted much attention in developing more effective catalysts for isocyanate trimerization. A number of catalysts for the trimerization of isocyanates have been extensively studied and reported in academic literature, including among others tetrabutylammonium fluoride (TBAF), 2-phosphaethynolate anion (OCP – ), sodium p -toluenesulfinate ( p -TolSO 2 Na)/tetrabutylammonium iodide (TBAI), , tetrakis­(dimethylamino)­ethylene (TDAE), proazaphosphatrane, N-heterocyclic carbenes, olefins, , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since the trimerization of isocyanate occurs easily and controllably to form a clear trifunctional isocyanate ring, this reaction is an ideal candidate for the synthesis of a clear polymer network [ 3–5 ]. The trimer reaction of isocyanate can be used to prepare many kinds of materials, such as resin [ 6 ], foams [ 7 ], aerogel [ 8 , 9 ], hydrogel [ 10 , 11 ], polyurethane gradient material [ 12 , 13 ], shape memory material [ 14 ], etc. and it has been applied to aerospace, aviation, biology, medicine, shipbuilding and other fields.…”
Section: Introductionmentioning
confidence: 99%